Compact Core Loss Model Based on an Effective Frequency for Arbitrary Core Excitations including DC-Bias - Stenglein, Erika; Albach, Manfred; Dürbaum, Thomas (2020 22nd European Conference on Power Electronics and Applications, EPE 2020 ECCE Europe, 2020)
To predict core losses for arbitrary excitations, the quasi-static energy losses depending on the swing and the DC-bias of the magnetic flux density are multiplied by an effective frequency. Measurement results for various shapes of the magnetic flux density (e.g. sinusoidal and triangular waveforms) with and without DC-bias verify this compact model.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Magnetic device; Measurement; Modelling; Passive component